Peran Public Relations untuk Meningkatkan Citra Perusahaan - Rina Sanra Fitriani; Dadan Mulyana (UNISBA Press, 2021)
Abstract. The increase of electricity payment bill in Bandung City in June 2020 has caused complaint in both social media, WhatsApp and also PLN’s payment office because the public was shocked and felt a loss knowing that they have to pay the bill three times higher than the usual in June. Due to many complaints that have been received, PLN of Bandung City tried to clarify and explain to the public about the increase of electricity payment bill with the aim to build a positive image and to recover PLN’s bad reputation so that no further complaints will occur. The important role of public relations is needed to handle this kind of case since the role of public relations is to create good communication between the public and PLN. In this COVID-19 situation, this research attempts to identify the role of PLN’s public relations in recovering the company’s image from the increase of electricity payment bill case from PT. PLN (Persero) of Bandung City in COVID-19 situation. Specifically, this research aimed to identify the obstacle that PLN’s public relations face in recovering their company’s image due to the rise of electricity payment bill in Bandung City case happened in this COVID-19 situation and also to explore why PLN’s public relations should recover their company’s image after the case happened. This research used the qualitative method, which is Robert K. Yin case study with type I research design that focused on a case with a unit of analysis using interviewees as the key informants of this research. Drawing conclussions the implementation of communication public relations pln in dyadic communication, triadic communication, and global network can strengthen a good relationship with people who are komplen. And reason public relations pln use reducing offensiveness of the event, corrective action, and mortification at the message of memes to can hasten understanding information about change tariff electricity for the komplen. Abstrak. Adanya kasus keluhan masyarakat tersebut pihak PLN kota Bandung berusaha mengklarifikasi dan menjelaskan kepada masyarakat mengenai kenaikan tarif listrik dengan tujuan agar membangun citra positif serta mengembalikan reputasi buruk PLN di mata masyarakat agar tidak terjadi complain berikutnya. Peran penting public relations sangat dibutuhkan untuk menciptakan komunikasi antara masyarakat dengan PLN berjalan dengan baik sesuai dengan harapan PLN, kondisi seperti ini pihak public relations PLN harus bisa mengendalikan kasus kenaikan tarif di tengah covid-19. Tujuan penelitian untuk mengetahui peran public relations PLN dalam memperbaiki citra dari kenaikan tarif listrik PT. PLN (Persero) area Kota Bandung pada masa Covid-19. Mengetahui kegitaan komunikasi public relations PLN dalam memperbaiki citra dari kenaikan tarif listrik PT. PLN (Persero) area Kota Bandung pada masa Covid-19. Mengetahui dimana letak hambatan yang terjadi pada public relations PLN dalam memperbaiki citra dari kenaikan tarif listrik PT. PLN (Persero) area Kota Bandung pada masa Covid-19, mengetahui mengapa public relations PLN harus menciptakan pemulihan citra dengan pesan meme tentang kenaikan tarif listrik PT. PLN (Persero) area Kota Bandung pada masa Covid-19. Metode penelitian kualitatif, studi kasus Robert K. Yin desain penelitian tipe 1 berfokus pada satu kasus dengan satu unit analisis menggunakan wawancara narasumber sebagai key informan penelitian. Simpulan dengan adanya kegiatan komunikasi public relations PLN secara dyadic communication, Triadic communication, dan global network dapat memperkuat hubungan yang baik dengan masyarakat yang komplen. Serta alasan public relations PLN menggunakan reducing offensiveness of event, corrective action, dan mortification pada pesan meme untuk dapat mempercepat pemahaman informasi tentang perubahan tarif listrik bagi masyarakat komplen.